Photochromic effect and photoconductivity in undoped and doped Bi₁₂SiO₂₀ crystals - Panchenko, T.V.; Strelets, K.Yu. (Condensed Matter Physics, 2007)
Photoinduced phenomena in the sillenite family crystals Bi₁₂MO₂₀ (BMO, with M = Si, Ti,
Ge) are studied intensively because these crystals are widely used as functional media in different types of light-modulating devices. So, the study of photoinduced processes and their modification by doping is very important in these applications. At present, the effect of different doping ions on optical and photoelectric properties has been studied on Bi₁₂MO₂₀ (BTO) crystals only [1–5]. It is shown, in particular, that Cu – ions consider-
ably increase the photochromic effect (PCE) in the visible range of spectra and decrease PCE in IR [1,6,7]. Mo-ions reduce the relaxation time of photoinduced optical absorption [5,7]. Nevertheless, the PCE mechanisms have not been studied well enough. It seems that unified investigations of PCE and photoconductivity (PC) can provide useful information in solving this problem. In the present paper, the results of investigations of PC and PCE in Bi₁₂MO₂₀ (BSO) crystals doped by Cu-, Ag- and Mo-ions are presented. У спектральному дiапазонi 0.5–3.5 eV дослiдженi стацiонарнi i фотоiндукованi спектри оптичного поглинання i фотопровiдностi, чистих i легованих iонами Cu, Ag i Mo кристалiв Bi₁₂MO₂₀. Спостерiгали вплив легування на фотохромний ефект i iндуковану фотопровiднiсть, отримали температурнi залежностi фотоiндукованого оптичного поглинання i фотопровiдностi. Показана вiдсутнiсть кореляцiї у спектральному розподiлi i у температурнiй залежностi обох ефектiв.